Considerations and analysis of the implementation of oncogeriatrics in Chile and its importance: Review of current literature - Honorato, Macarena; Calderón, Oscar; Rojas, Verónica; Fasce, Gerardo; Bartolotti, Constanza; Caglevic, Christian (Frontiers in Aging, 2023)
The Chilean census of 2017 reported that 11.4% of the local population are 65 years or older, and according to the National Institute of Statistics (INE) the current expectancy of life in Chile is 76 years for men and 81 years for women respectively . Cancer in Chile is a major public health problem. Aging is a significant risk factor for cancer development which added to the improved life expectancy, it increases the incidence of cancer. In 2040, new cancer cases will increase from 19.3 to 30.2 million worldwide . Older people are a heterogeneous group requiring specialized and individualized management. Chronological age does not necessarily correlate with physiological age. More than half of the geriatric patients with cancer have at least one comorbidity which is relevant when defining a cancer treatment . Likewise, polypharmacy is frequent and is an important issue to consider in people with cancer due to the risk associated with drug interactions . Oncogeriatric assessment consists of a comprehensive multidimensional evaluation, including functional and biopsychosocial issues, addressing aspects of the neoplastic disease such as the risk of toxicities due to systemic therapy and life expectancy . This tool has proven to be helpful in the diagnosis of conditions that are not evident in a routine oncological evaluation , such as geriatric syndromes, frailty, functional dependence, and cognitive impairment among others, which have an impact when deciding on therapy, predicting risks of treatment toxicity and mortality .